Fatigue in Pediatric Cancer Patients Undergoing Chemotherapy: A Cross-Sectional Study - Adelia, Gita; Putri, Fathia Manda Aiza; Putri, Veni Dayu; Arfina, Angga (Jurnal Kesehatan, 2025)
Fatigue is one of the most common and significant side effects experienced by children undergoing chemotherapy for cancer. This condition not only affects the child's physical state but also significantly impacts their overall quality of life. However, the assessment of fatigue levels in pediatric patients often remains a low priority in clinical services. This study aimed to describe the level of fatigue among pediatric cancer patients after chemotherapy at the Seruni Polyclinic, Arifin Achmad Regional General Hospital, Riau Province. This was a quantitative study with a cross-sectional design. The sampling technique used was purposive sampling, involving 59 children diagnosed with cancer, having received chemotherapy more than once, aged 1–15 years, and willing to participate in the study. The instrument used was the Fatigue in Pediatric Oncology–Allen (FOA-A) questionnaire, which has been validated (r=0.509–0.884) and tested for reliability (r=0.948). Data were analyzed using univariate analysis and presented in frequency distribution tables. The results showed that most respondents were in the preschool age group (33.9%) and male (52.5%). The most common type of cancer was leukemia (66.1%). A total of 64.4% of respondents had undergone 4–6 cycles of chemotherapy, and 61% had received chemotherapy for ≥6 months. Fatigue levels indicated that 62.7% of respondents experienced fatigue. The majority of pediatric cancer patients post-chemotherapy experienced fatigue. These findings emphasize the importance of regular fatigue assessments and the need for structured nursing interventions to reduce its negative impact on children’s quality of life.